Integrated Chinese Level 1 Part 1 : Textbook. Simplified Characters - Liu Yuehua, ....-; Yao Tao-chung, ....- (Boston : Cheng & Tsui, 2013)
This new edition of Integrated chinese is an outstanding achievement. Complete with interesting cultural notes, useful authentic materials, and a wealth of interactive exercises, the authors have outdone themselves AGAIN!
Keywords: Chinees